Energy-Saving Algorithm and Simulation of Wireless Sensor Networks Based on Clustering Routing Protocol - Wei He (IEEE Access, 2019)
An efficient and energy-saving algorithm, K-means and FAH (KAF), has been proposed to solve the problems of node energy constraints, short network cycle and low throughput in current wireless sensor networks. Network clustering is obtained by optimizing K-means clustering. Based on FAHP (Fuzzy Analytic Hierarchy Process) method, the cluster head selection is optimized considering the factors of node energy, distance from base station and energy efficiency of nodes. Based on the factors of transmission distance, energy and hop number, multi-hop routing is constructed to effectively reduce the energy consumption of nodes in data transmission. The simulation results show that compared with other protocols, KAF algorithm has obvious advantages in reducing node energy consumption, prolonging network life cycle and increasing network throughput. And under different routing protocol, the performances of the algorithm are verified. By adjusting the size of the candidate node set selection area, the reliability of data transmission of the long-distance node is increased, and the energy consumption load of the near-distance node is reduced. At the same time, the use of opportunistic transmission strategies increases the reliability of data transmission. The simulation results show that the proposed protocol can effectively reduce the energy consumption of nodes and prolong the network life cycle.